Analisis Nilai Tambah Pengolahan Ikan Tuna (Studi Kasus Pada: Home Industry Rhoa Z Kota Ternate) - Mani, Orwin La; Kaddas, Fatmawati; Fatmawati, Mila (Universitas Khairun, 2024)
Simple processing of tuna catches can create added value. Production of tuna fish which is processed into fish floss and garo rica fish is also one of the superior products in the Rhoa Z Home Industry and has a relatively high selling price compared to other products. The aim of the research is to determine the income and added value of tuna fish processing obtained by Home Industry Rhoa Z. The method used in the research is the Hayami analysis method. The research results obtained on tuna fish processing products for fish floss products have an income of Rp. 51,456,108 fish floss in two sizes, 100 grams and 200 grams, 100 gram fish floss has an added value of IDR. 57,900 or 4.19% of production results. For 200 grams of fish floss, there is an added value of IDR. 41,800 or 1.39% of production results. Garo Rica fish has an income of Rp. 194,448,108 garo rica fish, there are also two sizes, 150 grams and 200 grams, 150 gram garo rica fish has an added value of Rp. 5,183 or 0.104% of production results. 200 gram Garo Rica fish has an added value of IDR. 23,713 or 0.30% of production results.Keywords: Value Added, Hayami Analysis, Tuna Fish Processing.Â